Predictions put into practice: a quasi-experimental evaluation of Chicago’s predictive policing pilot - Saunders, Jessica; Hunt, Priscillia; Hollywood, John S. (Journal of experimental criminology, 2016)
Objectives In 2013, the Chicago Police Department conducted a pilot of a predictive policing program designed to reduce gun violence. The program included development of a Strategic Subjects List (SSL) of people estimated to be at highest risk of gun violence who were then referred to local police commanders for a preventive intervention. The purpose of this study is to identify the impact of the pilot on individual- and city-level gun violence, and to test possible drivers of results. Methods The SSL consisted of 426 people estimated to be at highest risk of gun violence. We used ARIMA models to estimate impacts on city-level homicide trends, and propensity score matching to estimate the effects of being placed on the list on five measures related to gun violence. A mediation analysis and interviews with police leadership and COMPSTAT meeting observations help understand what is driving results. Results Individuals on the SSL are not more or less likely to become a victim of a homicide or shooting than the comparison group, and this is further supported by city-level analysis. The treated group is more likely to be arrested for a shooting. Conclusions It is not clear how the predictions should be used in the field. One potential reason why being placed on the list resulted in an increased chance of being arrested for a shooting is that some officers may have used the list as leads to closing shooting cases. The results provide for a discussion about the future of individual-based predictive policing programs.